2023
DOI: 10.3390/nu15030790
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus gasseri NK109 and Its Supplement Alleviate Cognitive Impairment in Mice by Modulating NF-κB Activation, BDNF Expression, and Gut Microbiota Composition

Abstract: Aging-related gut microbiota dysbiosis initiates gut inflammation and microbiota dysbiosis, which induce the occurrence of psychiatric disorders including dementia. The alleviation of gut microbiota dysbiosis by probiotics is suggested to be able to alleviate psychiatric disorders including cognitive impairment (CI). Therefore, to understand how probiotics could alleviate CI, we examined the effects of anti-inflammatory Lactobacillus gasseri NK109 and its supplement (NS, mixture of NK109 and soybean embryo eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
0
2
1
Order By: Relevance
“…Lee et al reported that Proteobacteria population and LPS levels were significantly higher in aged mice than in young mice [9]. Yun et al also reported that the gut microbiota of 5xFADtransgenic mice strongly increased Proteobacteria population and LPS production [42]. However, we found that oral administration of NK41, NK46, and NKc reduced LPS levels in the blood and feces of 5xFAD-transgenic or aged mice.…”
Section: Discussioncontrasting
confidence: 65%
“…Lee et al reported that Proteobacteria population and LPS levels were significantly higher in aged mice than in young mice [9]. Yun et al also reported that the gut microbiota of 5xFADtransgenic mice strongly increased Proteobacteria population and LPS production [42]. However, we found that oral administration of NK41, NK46, and NKc reduced LPS levels in the blood and feces of 5xFAD-transgenic or aged mice.…”
Section: Discussioncontrasting
confidence: 65%
“…Therefore, it has been used as a potential treatment to alleviate psychiatric disorders, including cognitive impairment (CI; Azad et al, 2018 ). Lactobacillales as a probiotic has been widely used in various CI-related studies, and a study was conducted to induce the expression of brain-derived neurotropic factor (BDNF), inhibit NF-κB activation, and regulate GM in mice to alleviate CI accompanied by systemic inflammation through Lactobacillus griseus ( Yun et al, 2023 ). A systematic evaluation showed increased levels of brain-derived neurotrophic factor, improved inflammatory profile, and cellular biomarker modulation in patients with dementia taking probiotic Lactobacillus ( Ruiz-Gonzalez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of NK109 and heat-processed SE mix increased cognitive function in aged mice (Yun et al, 2023). Therefore, to investigate whether SE could increase the CI-ameliorating effect of NK109, we investigated the effects of N L , S E N L , and S E N H on LPS-induced CI in mice (Fig.…”
Section: The Combined Effects Of Nk109 With Se On Lps-induced CI and ...mentioning
confidence: 99%